Pengaruh Pembelajaran Berbasis Proyek terhadap Keterampilan Berpikir Kritis Peserta Didik di SMP Negeri 1 Wayer - Nasib, Nasib; Jasruddin, Jasruddin; Arsyad, Muhammad (Indonesian Journal of Social and Educational Studies, 2024)
Abstract. This research is pre-experimental research that aims to analyze whether there is an influence of critical thinking skills on students who are taught using a project-based learning model at SMP Negeri 1 Wayer. The independent variable in this research is project-based learning, while the dependent variable is critical thinking skills. The number of samples in this research was 14 students in class VII at SMP Negeri 1 Wayer. The research data was obtained by giving a critical thinking skills test on temperature and heat material as a pretest and posttest. The data analysis technique for testing hypotheses uses Normalized Gain (N Gain). Based on the Normalized Gain (N Gain) calculation carried out, the N Gain value was 63.54, so the N Gain value is in the medium category, meaning that there is a significant increase in critical thinking skills in students who are taught using project-based learning at SMP Negeri 1 Wayer. Keywords: Critical Thinking, Project Based Learning, Pre-experiment